Pengaruh Literasi Ekonomi dan Pengalaman Prakerin terhadap Minat Berwirausaha Peserta Didik Kelas XI Kompetensi Keahlian Administrasi Perkantoran (APK) SMK Negeri 1 Pogalan Tahun Pelajaran 2017/2018 - Yahya Reka Wirawan, Flora Puspitaningsih (Universitas PGRI Madiun, 2019)
This study aims to determine whether there is influence either partially or simultaneously between economic literacy and prakerin experience of entrepreneurship interest of class XI students of Office Administration (APK) program of SMK Negeri 1 Pogalan year lesson 2017/2018. This research is a quantitative research. Population in this research is class XI student of Office Administration skill program (APK) amounting to 73 students. Sampling technique by nonprobability sampling. Samples in this study were 73 students. Data analysis techniques using SPSS Version 23.00 For Windows. The result of data analysis in this research shows that can be concluded that there is a significant influence between economic literacy and prakerin experience of entrepreneurship interests kelsi XI skill program Administrative Office (APK) SMK Negeri 1 Pogalan year lesson 2017/2018. Overall influence of economic literacy and prakerin experience to entrepreneurship interest equal to 21,6%, while the rest equal to 78,4% influenced by other factors outside of variable in this research. The results of this study can be used as input and consideration material for learners, teachers and institutions to improve the quality of education and inculcate entrepreneurship interests in learners and can serve as a reference for further research by developing existing research.